Reclaiming distributed cognition in networked learning: An inter-subjective, socio-material perspective - Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2016)
On the tenth anniversary of the networked learning conference I am looking back at developments in identifying the sites of learning in networked learning design and praxis. Beginning with McConnell’s (1998) premise that collaboration is central to the development of democratic ‘learning communities’ and Jones’ (2000) relational perspective on the role of technologies in connecting learners, tutors, and learning resources, I examine early critiques of community and the implications of those critiques for design, tutoring, and assessment practices. I then turn to a discussion of interrelated human and technological agencies and a historical trajectory of design foci at the resource, task, and activity levels. Tensions between research orientations that focus on individual learning and those that focus on collective learning are traced to associated theoretical perspectives and methodological choices. The construct of the individual mind and the notion of connectivism are critiqued. The agencies of socially constructed technologies to distribute learning capacities across networks are examined for insights into and implications of differing approaches to collective coordination of social-material practices. In concluding this retrospective, I return to the critical and humanistic roots of networked learning and introduce Hodgson, de Laat, McConnell, and Ryberg’s (2014) call to “transcend the dualism between abstract mind and concrete material social practice” (p. 3). I use discourse analysis to critique contemporary cognitivist, computational conceptualizations of the individual mind and the resultant focus on instructionalist underpinnings in broader educational technology approaches to design. I argue that this perspective on cognition is reductive: focused on teacher-designer-researcher control, hierarchical perceptions of learning contexts, and suggest the quest for designed orchestrations of learning processes has led to an assumption that the efficaciousness of learning can simply reside in resources. The computational, cognitivist perspective on design is contrasted with Conole’s (2006) rejection of resource-level foci on design and with Goodyear, Carvalo, and Dohn’s (2014) distinctions among designable tasks and emergent activities; situated conceptualizations of affordances and mutually constitutive perspectives on the relationships among material social practices and learning. The “reclaiming” section of the paper examines three pre-computational conceptualizations of distributed cognition as embodied, integrated with socio-material artifacts, and enacted through practices. I conclude with looking forward to a time where pre-computational conceptualizations of distributed cognition provide links to networked learning theory, a route to transcending dualisms, and opens new examinations and problematizations.